2012
DOI: 10.1177/0194599812463320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postoperative Aspirin on Outcomes in Microvascular Free Tissue Transfer Surgery

Abstract: Postoperative thromboprophylaxis with aspirin after microvascular free tissue transfer does not provide an improvement in free flap survival and may be associated with a higher complication rate. Prospective, randomized studies are required to elucidate the role of postoperative pharmacotherapy for prophylaxis against microvascular thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 25 publications
3
102
0
1
Order By: Relevance
“…153 A recent retrospective analysis of 309 free flaps from the head and neck microvascular groups have suggested that postoperative anticoagulation with any anticoagulation (e.g., aspirin, lowmolecular-weight heparin, heparin drip) does not offer protective effects for microvascular thrombosis and increases complication rates (Level IV Evidence). 154 Selection of patients in treatment arms was not randomized and was unclear. The landmark multicenter prospective free flap study by Khouri et al discovered that only postoperative subcutaneous heparin had a significant preventative effect on flap thrombosis (Level I Evidence).…”
Section: Postoperative Protocols Anticoagulationmentioning
confidence: 99%
“…153 A recent retrospective analysis of 309 free flaps from the head and neck microvascular groups have suggested that postoperative anticoagulation with any anticoagulation (e.g., aspirin, lowmolecular-weight heparin, heparin drip) does not offer protective effects for microvascular thrombosis and increases complication rates (Level IV Evidence). 154 Selection of patients in treatment arms was not randomized and was unclear. The landmark multicenter prospective free flap study by Khouri et al discovered that only postoperative subcutaneous heparin had a significant preventative effect on flap thrombosis (Level I Evidence).…”
Section: Postoperative Protocols Anticoagulationmentioning
confidence: 99%
“…Two studies [15],[17] compared aspirin and heparin for the prevention of flap loss, and the ORs of the 2 studies were 1.688 and 2.087, respectively (Figure 2). There was heterogeneity in the combined OR of the 2 studies (Q = 0.052, I 2  = 0%, p  = 0.819); therefore a fixed-effects model of analysis was used.…”
Section: Resultsmentioning
confidence: 99%
“…Patients undergoing head and neck free flap reconstruction are often anticoagulated postoperatively. Anticoagulation is associated with postoperative hematoma formation, although almost always at a surgical site [8]. …”
Section: Discussionmentioning
confidence: 99%